Dental anomalies prevalence in children born from HIV seropositive mothers dental anomalies in HIV children - Bertazzoli, Rita CB; Baptista, Maria R; Fonseca, Luciana C; Figueiredo, Claudia RL (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: many researches has well documented the presence of the oral manifestations in pediatric aids, nevertheless, very few studies show therelationship of the HIV infection and the use of antiretroviral drugs and the presence of dental anomalies. Objective: to verify the dental shape, num-ber, size and position anomalies prevalence in HIV positive children contaminated by vertical route and under antiretroviral therapy. Methods: it is acase-control, cross-sectional, descriptive study with data obtained from HIV-infected and uninfected children through panoramic radiographs. All ofthem were born from HIV-positive mothers. Informations about use of antiretroviral therapy were obtained from medical records. The results of bothgroups were statistically compared. Results:the results showed the presence of anomalies of number (2,2%), size (2,2%) and position (6,5%) at theinfected children group and dental anomalies of number (3.3%) and position (3,3%), at the uninfected group, but there was no statistical significantdifference between the groups. Conclusion:although the disturbance of dental position (giroversion) had been more prevalent in HIV infected chil-dren, it was possible to conclude that there was no statistical significant relationship between the HIV infection and the use of antiretroviral drugswith the presence of dental anomalies.